درجة توفر متطلبات تحقيق الهدف الرابع من أهداف التنمية المستدامة لعام 2030 في مرحلة التعليم الأساسي (دراسة ميدانية في مدارس مدينة طرطوس) (Journal of Hama University, 2025)
The research aimed to identify the degree of availability of requirements for achieving the fourth goal of the Sustainable Development Goals for the year 2030 in the basic education stage in the city of Tartous. The research sample consisted of (327) principals and teachers, according to the research variables (job title, academic qualification, teaching experience), and to achieve the goal In the research, the researcher followed the descriptive analytical method, and used a questionnaire consisting of (28) items, which included three dimensions (requirements for achieving quality education, requirements for achieving equitable and comprehensive education for all, requirements for enhancing lifelong educational opportunities for all), and the results were as follows:- The degree of availability of requirements for achieving the fourth goal of the Sustainable Development Goals for the year 2030 at the basic education stage from the point of view of principals and teachers in schools in the city of Tartous is medium, with an arithmetic mean (3.28) and a standard deviation (0.967).- There are no statistically significant differences between the average scores of the research sample members on a questionnaire that provides the requirements for achieving the fourth goal of the sustainable development goals due to the job title variable.- There are statistically significant differences between the average scores of the research sample members on a questionnaire that provides the requirements for achieving the fourth goal of the sustainable development goals due to the academic qualification variable, and in favor of postgraduate studies.-There are no statistically significant differences between the average scores of the research sample members on a questionnaire that provides the requirements for achieving the fourth goal of the sustainable development goals due to the variable of teaching experience.In light of its findings, the current research suggested the need to work on developing a detailed plan to enhance sustainable development practices in schools in the Syrian Arab Republic, and to enhance ways of partnering with the private sector to provide the necessary funding to increase investment in infrastructure and equip schools with the necessary technological devices.